1998
DOI: 10.1007/bf03011987
|View full text |Cite
|
Sign up to set email alerts
|

The laryngeal mask airway reduces blood flow in the common carotid artery bulb

Abstract: The laryngeal mask airway reduces blood flow in the common carotid artery bulb Purpose: The introduction of the laryngeal mask airway (LMA) has had a major impact on anaesthetic practice in the last ten years. Previous authors have demonstrated pressures equivalent to mean arterial blood pressure within the cuff of the LMA. This study examined the effects of cuff inflation on the cross sectional area, flow and velocity of blood flow at the level of the carotid sinus.Methods: Seventeen patients scheduled to hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“… 3,4,7 A recent study demonstrated that inflation of the LMA cuff results in a decrease in both the cross‐sectional area of and blood flow through the common carotid artery bulb. 8 However, no information about intracuff pressures was available in the study.…”
Section: Discussionmentioning
confidence: 99%
“… 3,4,7 A recent study demonstrated that inflation of the LMA cuff results in a decrease in both the cross‐sectional area of and blood flow through the common carotid artery bulb. 8 However, no information about intracuff pressures was available in the study.…”
Section: Discussionmentioning
confidence: 99%
“…The cross-sectional area of both carotid arteries significantly decreased after inflation of the LMA cuff which was compensated for by an increase in flow velocity and carotid blood flow. In their subsequent study, the authors evaluated carotid artery hemodynamics in seventeen patients who had cLMA inserted for routine elective cases under general anesthesia [ 119 ]. The cross-sectional area of the carotid arteries significantly differed between cuff inflation and deflation.…”
Section: Effect Of Sgas On Cervical Vascular Structuresmentioning
confidence: 99%
“…This led the authors to abandon the KA as a primary airway and to begin to look at the effect on survival of airway choice and to the hypothesis that supraglottic airways may have a detrimental effect on cerebral perfusion. Colbert, et al demonstrated that with a laryngeal mask airway carotid flow was marginally decreased in patients with a normal perfusion state [7]. The authors were concerned that in the low perfusion state of CPR that the effect would be greater.…”
Section: Discussionmentioning
confidence: 99%